CHILD-FRIENDLY ISLAMIC BOARDING SCHOOL: INTEGRATION OF CHILD PROTECTION LAW AND ISLAMIC FAMILY LAW - Asyhari Zubair; Jalaludin Faruk Azhari; Machbub Ainurrofiq (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
Violence against children in Islamic boarding schools, including physical, psychological, and sexual abuse, remains a serious issue that contradicts Islamic values. This study aims to examine the implementation of hifzu al-nafs and hifzu al-'aql within the framework of maqashid shari'ah as the foundation for child-friendly Islamic boarding schools and to analyze their integration with Indonesian child protection and pesantren laws. A qualitative phenomenological approach was conducted at Al-Falah Bellud Tlanakan Islamic Boarding School, Pamekasan. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The findings indicate that the pesantren has implemented hifzu al-nafs through anti-violence policies, complaint mechanisms, and psychological support, while hifzu al-'aql is realized through curriculum integration and the mudzakarah method. Nevertheless, normative, institutional, and cultural gaps remain. The study proposes an integrative child-friendly pesantren model based on maqashid shari'ah to strengthen child protection and educational practices.